Unmet needs, quality of life and psychological distress: insights regarding head and neck cancer patients in a rural setting. Issue 1 (21st September 2022) - Sunderland, M; Matthews, C; Waterhouse, D; Shetty, S; Morton, R P
Abstract: Objective: This study aimed to evaluate the perceived quality of life, unmet needs and psychological distress in patients with head and neck cancer in a rural setting in New Zealand. Method: Patients presenting with head and neck cancer in Northland, New Zealand, were asked to complete questionnaires on quality of life, unmet needs, and anxiety or depression together with a free-text option. Results: About one quarter of respondents (27 per cent) scored high in the anxiety and depression scale, with corresponding diminished quality of life scores and increased needs. Over half of respondents (54 per cent) found it challenging to travel for treatment. Financial difficulties were encountered more frequently with indigenous patients. Rurality alone does not lead to significant differences in quality of life or needs. Conclusion: After treatment for head and neck cancer, it is important to monitor and manage patients' psychological distress and ease of access to health services to improve quality of life.